Integrating Sukarara Traditional Weaving into Chemistry Education: Impact on Students’ Cultural Literacy and Critical Thinking Skills: English - Astuti, Mei Dewi; Hendrawani; Khaeruman (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Chemistry is often perceived by students as an abstract science disconnected from their cultural heritage. In Lombok, the traditional weaving craft of Sukarara Village contains rich chemical principles, particularly in natural dyeing and mordanting processes. This study aims to investigate the relationship between students’ critical thinking perceptions and their cultural literacy within the context of Sukarara’s ethno-chemistry. A quantitative correlational design was employed, involving 47 high school students. Data were collected using validated questionnaires for critical thinking (Cronbach’s Alpha = 0.750) and cultural literacy (Cronbach’s Alpha = 0.824), which integrated local wisdom indicators from Sukarara weaving. Data analysis using Pearson Product-Moment Correlation revealed a weak negative correlation (r = -0.249) with a significance value of 0.092 (p > 0.05). Furthermore, simple linear regression analysis confirmed that critical thinking did not significantly influence cultural literacy (t = -1.723, p = 0.092). These findings highlight a "literacy paradox," where students’ general critical thinking abilities do not automatically translate into an understanding of the chemical principles embedded in their cultural heritage. The study concludes that fostering cultural literacy requires explicit pedagogical integration and specialized ethno-chemistry modules rather than relying solely on general cognitive skills.